Study of age-related changes in Middle ear transfer function. Issue 13 (3rd October 2019) - Zhou, Lei; Shen, Na; Feng, Miaolin; Liu, Houguang; Duan, Maoli; Huang, Xinsheng
Abstract: Osteoporosis (OP) is common with advancing age. Several studies have shown a strong correlation between OP and otosclerosis. However, no studies have investigated OP of the malleus, incus or stapes in the human middle ear, its effect on middle ear transfer function. Here, we investigate whether these three ossicles develop OP, and how this affects middle ear transfer function. The effect of OP on middle ear transfer function was investigated in simulations based on a finite element (FE) method. First, the FE model used in our previous study was refined, and optimized by introducing viscoelastic properties to selected soft tissues of the middle ear. Then, the FE model was used to simulate OP of the three ossicles and assess its influence on middle ear transfer function. Other possible age-related changes, such as stiffness of the joints or ligaments in the middle ear, were also investigated. The results indicated that OP of the ossicles could increase the high frequency displacement of both the umbo and stapes footplate (FP). However, the stiffness of the middle ear soft tissue can lead to the decrease of middle ear gain at lower frequencies. Furthermore, loosening of these joints or ligaments could increase displacement of the umbo and stapes FP. In conclusion, although age-related hearing loss is most commonly conceived of as sensorineural hearing loss (SNHL), we found that age-related changes may also include OP and changes in joint stiffness, but these will have little effect on middle ear transfer function in elderly people.